2010
DOI: 10.1007/s11060-010-0211-z
|View full text |Cite
|
Sign up to set email alerts
|

Chordoid meningioma: a clinicopathologic study of 11 cases at a single institution

Abstract: Chordoid meningioma is an uncommon variant of meningioma, which histologically bears a great resemblance to chordoma and often follows an aggressive clinical course. We examine clinicopathologic features of 11 cases of this rare tumor to further elucidate its behavior. Thirteen specimens of chordoid meningioma belonging to 11 patients were obtained at a single institution from 1995 to 2009. Correlations of histologic parameters, immunohistochemical study, and clinical features were assessed. This series includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 33 publications
6
43
3
1
Order By: Relevance
“…In addition, most lymphocyte infiltrates in our meningiomas consisted of T cells. This differed from the report of Kepes [4][5][6][7][8][9][10][11].4%, mean = 5.2%) in their series and also reported a high rate of recurrence (39%). 1 Lilia et al reported a recurrence rate of 70% with a relatively narrow range in the MIB-1 labeling index (6.0-9.0%, mean = 7.3%).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In addition, most lymphocyte infiltrates in our meningiomas consisted of T cells. This differed from the report of Kepes [4][5][6][7][8][9][10][11].4%, mean = 5.2%) in their series and also reported a high rate of recurrence (39%). 1 Lilia et al reported a recurrence rate of 70% with a relatively narrow range in the MIB-1 labeling index (6.0-9.0%, mean = 7.3%).…”
Section: Discussioncontrasting
confidence: 93%
“…So far, 130 patients with these tumors have been described in the English literature, largely in the form of isolated case reports, with the exception of five series (one series published in 2010 by our hospital analyzed 11 patients from 1995 to 2009). [1][2][3]9,11 Kepes et al published the first series of CM in 1988 with an emphasis on chordoma-like histology, young age, prominent peritumoral lymphoplasmacellular infiltrates, and association with systemic manifestations of Castleman syndrome. 3 They described occurrence in young individuals, chordoma-like histological appearance, peritumoral lymphoplasmacellular infiltrates with B cell predominance, and an association with the systemic manifestations of hematological conditions, including iron-refractory hypochromic/microcytic anemia and bone marrow plasmacytosis with dysgammaglobulinemia (Castleman's syndrome).…”
Section: Discussionmentioning
confidence: 99%
“…A little more than 100 cases of chordoid meningioma have been described in the English-language literature, the majority of which are in the pathology and neurosurgery literature. [4][5][6][7][8][9] Attempts to distinguish benign from atypical and malignant meningiomas have been undertaken with variable results, and DWI and ADC values have provided the most reliable means of differentiation, 10,11 though no data analysis specifically examining the chordoid morphologic variant has been performed. To the best of our knowledge, only 3 case reports in which the MR imaging characteristics of chordoid meningiomas were described have been published in the radiology literature.…”
Section: Resultsmentioning
confidence: 99%
“…CM is a rare variant of meningioma that is characterized by epithelioid cord-like tumor cells in the myxoid stroma (4,9). CM has been recognized as an aggressive tumor of meningothelial origin and is considered to be a grade II lesion, in addition to clear cell and atypical meningioma, due to a high rate of recurrence, particularly following subtotal resection.…”
Section: Discussionmentioning
confidence: 99%